Effects of litter size and piglet sex on gestation length in Landrace pigs - Sari, Merry Friana; Tarsisius Considus Tophianong; Yohanes Timbun Raja Mangihut Ronael Simarmata; Heny Nitbani (Universitas Airlangga, 2025)
This study aims to investigate the relationship between litter size and piglet sex with gestation length in Landrace pigs. The research was conducted at a farm in Kupang, East Nusa Tenggara, involving 15 healthy Landrace sows monitored from December 2024 to February 2025. The methodology employed included the collection of primary data through direct observation and secondary data obtained from farm records. The results indicated that the average (±SD) gestation length for Landrace pigs was 113.53 ± 0.64 days, with a variation ranging from 113 to 115 days. Statistical analysis using the Spearman correlation test revealed no significant correlation between litter size and gestation length (p values= 0.115; p >0.05). These findings suggest that physiological adaptations in Landrace pigs maintain a consistent gestation length regardless of litter size. Additionally, factors such as maternal nutrition, environmental conditions, and management practices were identified as potential influencing factors. The study also found no correlation between piglet sex and gestation length, with p-values of 0.89 for male piglets and 0.602 for female piglets. Overall, the results indicate that neither litter size nor piglet sex are primary factors determining the length of gestation in Landrace pigs.